Direct Connection of Supercapacitor-Battery Hybrid Storage System to the Grid-tied Photovoltaic System - Perdana, Yoga; Muyeen, S. M.; Al-Durra, Ahmed; Simoes, Marcelo; Morales-Paredes, H. K. (Institute of Electrical and Electronics Engineers (IEEE), 2018)
Penetration rate of grid-connected photovoltaic (PV) generation to the existing utility grid is rapidly increasing over the years. Since the power generated from PV systems fluctuate according to the weather condition, e.g., cloud passing, this can significantly disturb the stability of a weak utility grid. The integration of energy storage devices and its ramp-rate control technique are required to reduce the impact of PV systems output fluctuations and augment the stability of the utility grid. In this paper, ramp-rate control is applied to the direct connection of energy storage devices in PV generation system configuration. The direct connection of supercapacitors string and battery combination scheme is proposed to reduce the number of power converters so that the efficiency of the system is increased. In this work, the PV system output is controlled by directly control the energy storage system (ESS) to limit the changing rate of PV output to desired ramp-rate value. Hence, reducing the battery charge/discharge cycles and extending the expected lifetime of the ESS. The performance of the proposed direct connection scheme of ESS and its ramp-rate control strategy is verified using a 1-kW PV system prototype.
Keywords: Batteries; hybrid energy storage; Inverters; Mathematical model; Maximum power point trackers; MPPT; Photovoltaic; Photovoltaic systems; ramp-rate control